Intracellular delivery of cytochrome c by galactosylated albumin to hepatocarcinoma cells. (14th April 2014) - Yeh, Tzyy-Harn; Wu, Fe-Lin Lin; Shen, Li-Jiuan
Abstract: In some cancer cells, translocation of cytochrome c (Cyt c) from mitochondria to the cytoplasma is inhibited. This inhibition prevents cells from undergoing apoptotic cell death and can lead to uncontrolled cell growth. Increasing cytoplasmic concentration of Cyt c can induce apoptosis in cancer cells as a strategy of cancer therapy. Here we proposed a galactosylated albumin based carrier for intracellular delivery of Cyt c to hepatocarcinoma cells. Galactosylated albumin is recognized by highly expressed asialoglycoprotein receptors (ASGPR) on hepatocarcinoma cells and is further internalized into cells via receptor mediated endocytosis. Cyt c was chemically conjugated to galactosylated albumin with a reducible disulfide linker in order to release Cyt c from the carrier inside cells. We tested cellular uptake and cytotoxicity of Cyt c conjugates in ASGPR positive and negative hepatocarcinoma cells. The results showed galatosylated albumin significantly increased cellular uptake in both cell types resulting in cytotoxicity in a dose dependent manner through the induction of apoptosis. The lack of ASGPR specific uptake might be due to other carbohydrate-recognizing receptors expressed on tumor cells. In general, our work has shown that intracellular delivery of Cyt c to tumor cells can be an alternative therapeutic approach and galactosylated albumin can be a protein drug carrier for intracellular delivery.